Peningkatan Kualitas Produk dan Minimasi Pemborosan Dengan Mengunakan Pendekatan Six Sigma Pada Perusahaan Pakan Ternak - Katon Muhammad; Kukuh Winarso; Ida Lumintu (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2020)
PT. XYZ is one of the animal feed companies which has some of the largest production units in Indonesia. This Feed Company has several brands of products on the market. The company's production line is indicated to have a problem, namely product defects. Defective products caused by the production process and also the process of storing raw materials and finished materials in the company. Related to the six sigma in it has a phase of define, measure, analyze, improve and control phases, is chosen to overcome the existing problems. From the define, measure and analyze phase, it is known that there are significant defects, namely defects with flea attributes in the production process, textures, lumps, and ticks in the inventory. From the results of the RPN assessment, it is known that tick defects on the production line are valued at 168, text 105 and ticks in the production process 90 so that from the results of the assessment the RPN is given recommendations for improvement with consideration of the highest RPN value. The recommended improvement recommendations are the installation of blowers and air temperature regulators in the company's storage section, conduct a design of experiment in stages to select the best raw materials by considering the quality problems of the products produced and thirdly, the improvement of the cleaning schedule in the cooler, spoting and also rotex on production machines to minimize the cause of defects.